2007
DOI: 10.1051/vetres:2007034
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors forSalmonellaseroconversion of fattening pigs in farrow-to-finish herds

Abstract: -We did a prospective observational 9-month long study to quantify risk factors of managerial and hygiene practices, and pig-health status for Salmonella seroconversion of fattening pigs reared in subclinically infected French farrow-to-finish farms. During the fattening phase, 2 649 pigs belonging to the same batch of contemporary pigs, from 89 conventional farrow-to-finish farms were individually followed and regularly blood sampled on a monthly basis. Farm recruitment was based on the farmer's willingness t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 30 publications
1
36
2
1
Order By: Relevance
“…However, due to a variety of potential confounding factors related to the intestinal microbial ecology in the host (i.e., the pigs), the susceptibility/resistance characteristics of the Salmonella strain present (or introduced) in the herd, and also to the dose and route of administration of the drugs, reported results are usually inconsistent, particularly when trying to determine the potential role of specific antibiotics as risk factor for Salmonella (Beloeil et al, 2007;Farzan et al, 2006;Funk et al, 2007;Funk, LeJeune, Wittum, & Rajala-Schultz, 2006;Hotes et al, 2010;Leontides et al, 2003;Rajic, Chow, et al, 2007;van der Wolf et al, 2001). On-farm antibiotic use is only one factor affecting bacterial resistance, which is also affected by several other on-farm factors that also influence the emergence of resistant foodborne pathogens, such as Salmonella (Farzan, Friendship, Dewey, Poppe, & Funk, 2010;Varga, Rajic, McFall, Reid-Smith, & McEwen, 2009).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, due to a variety of potential confounding factors related to the intestinal microbial ecology in the host (i.e., the pigs), the susceptibility/resistance characteristics of the Salmonella strain present (or introduced) in the herd, and also to the dose and route of administration of the drugs, reported results are usually inconsistent, particularly when trying to determine the potential role of specific antibiotics as risk factor for Salmonella (Beloeil et al, 2007;Farzan et al, 2006;Funk et al, 2007;Funk, LeJeune, Wittum, & Rajala-Schultz, 2006;Hotes et al, 2010;Leontides et al, 2003;Rajic, Chow, et al, 2007;van der Wolf et al, 2001). On-farm antibiotic use is only one factor affecting bacterial resistance, which is also affected by several other on-farm factors that also influence the emergence of resistant foodborne pathogens, such as Salmonella (Farzan, Friendship, Dewey, Poppe, & Funk, 2010;Varga, Rajic, McFall, Reid-Smith, & McEwen, 2009).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%
“…In a field study, observed that seroconversion for L. intracellularis or for porcine reproductive and respiratory syndrome virus was associated with Salmonella shedding in finishing pigs. Moreover, Beloeil et al (2007) reported that seropositivity for porcine reproductive and respiratory syndrome virus was associated with a 1.6 (95% CI 1.1-2.5%) increased odds ratio for Salmonella seroconversion. Under experimental conditions, parasite infestation has also been shown to favor Salmonella infection and shedding in pigs (Steenhard et al, 2002).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the high Salmonella seroprevalence in the sows and increased rate of the seropositive slaughtered fattening pigs in 2009 thus suggests an epidemiological link in the latently infected herds. This variation in serological findings may be potentially explained by the season, changes in hygiene level, management, and other risk factors in the herds which might have affected the course of Salmonella infection and seroconversion in fattening pigs (Beloeil et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Salmonellosis along with being a public health concern, is a economic problem as it also affects livestock breeding [3,4]. 26.9% of the human cases in the EU are caused by contaminated pork meat [5][6][7][8]. The prevalence of the main serovars in pigs, S. Typhimurium and S. Derby, is estimated approximately to be 10.3% at the slaughterhouse [6].…”
Section: Introductionmentioning
confidence: 99%